2022
DOI: 10.1590/1980-5764-dn-2022-s104pt
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico do comprometimento cognitivo vascular: recomendações do Departamento Científico de Neurologia Cognitiva e do Envelhecimento da Academia Brasileira de Neurologia

Abstract: RESUMO Desde a publicação das últimas recomendações para o diagnóstico e tratamento da Demência Vascular pela Academia Brasileira de Neurologia em 2011, avanços significativos ocorreram na terminologia e critérios diagnósticos. O presente manuscrito é resultado do consenso entre especialistas indicados pelo Departamento Científico de Neurologia Cognitiva e do Envelhecimento da Academia Brasileira de Neurologia (2020-2022). O objetivo foi atualizar as recomendações práticas para a identificação, classificação e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 113 publications
(200 reference statements)
1
0
0
Order By: Relevance
“…In the systematic review with meta-analysis performed by Nielsen & Jørgensen 21 , it was observed that, in low- and middle-income countries, RUDAS results are less affected by schooling levels than MMSE. This observation regarding MMSE has also been found in its comparison with other instruments 44 .…”
Section: Discussionsupporting
confidence: 75%
“…In the systematic review with meta-analysis performed by Nielsen & Jørgensen 21 , it was observed that, in low- and middle-income countries, RUDAS results are less affected by schooling levels than MMSE. This observation regarding MMSE has also been found in its comparison with other instruments 44 .…”
Section: Discussionsupporting
confidence: 75%